A methanol extract of Scabiosa atropurpurea enhances doxorubicin cytotoxicity against resistant colorectal cancer cells in vitro - Ben Toumia, Imene; Sobeh, Mansour; Ponassi, Marco; Banelli, Barbara; Dameriha, Anas; Wink, Michael; Chekir Ghedira, Leila; Rosano, Camillo (Molecules, 2020)
Colorectal cancer is a malignancy with a high incidence. Currently, the drugs used in chemotherapy are often accompanied by strong side effects. Natural secondary metabolites can interfere with chemotherapeutic drugs and intensify their cytotoxic effects. This study aimed to profile the secondary metabolites from the methanol extract of Scabiosa atropurpurea and investigate their in vitro activities, alone or in combination with the chemotherapeutic agent doxorubicin. MTT assay was used to determine the cytotoxic activities. Annexin-V/PI double-staining analysis was employed to evaluate the apoptotic concentration. Multicaspase assay, quantitative reverse transcription real-time PCR (RT-qPCR), and ABC transporter activities were also performed. LC-MS analysis revealed 31 compounds including phenolic acids, flavonoids, and saponins. S. atropurpurea extract intensified doxorubicin anti-proliferative effects against resistant tumor cells and enhanced the cytotoxic effects towards Caco-2 cells after 48 h. The mRNA expression levels of Bax, caspase-3, and p21 were increased significantly whereas Bcl-2 expression level was decreased. Furthermore, the methanol extract reversed P-glycoprotein or multidrug resistance-associated protein in Caco-2 cells. In conclusion, S. atropurpurea improved chemosensitivity and modulated multidrug resistance in Caco-2 cells which makes it a good candidate for further research in order to develop a new potential cancer treatment.